ION-EXCHANGE PROPERTIES OF SILIKAGEL WITH IMMOBILISED ETHYLSULPHONIC ACID: UDC 543.62:543.21+541.183 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
Dуnamic ion-exchange properties of silica immobilized with covalent ethyl-sulphonic groups was studied. It was found that this ionexchanger had properties of strong-acid ionexchanger and adsorbed metals by electrostatic mechanism.
Keywords: -